The Perceived Self-Efficacy of Resource Rooms Teachers on Distance Learning Experience in Amman in Terms of Some Variables - Mirvat Y. Amirah; Khaldoun A. Najadat; Sara J. Mubarak (International Journal of Education, 2024)
This study aimed to examine the perceived self-efficacy of the resource room teachers for the distance learning experience in the capital Amman, Jordan in terms of some variables. To achieve this goal, 124 female resource teachers in government schools in the capital governorate were selected. The perceived self-efficacy measure was used to collect data. It is a valid and reliable measure that contains 25 items. The results showed that the level of perceived self-efficacy of the resource room teachers for the distance learning experience was moderate, as the mean of the overall tool was (3.16) with a moderate evaluation score. Table (3) shown that the averages of the tool's items ranged between (2.15-4.07). These averages didn't indicate statistically significant differences at (α≤0.05) for the variables: specialization, teacher's educational level, and number of students who receive service in the room. The data showed statistically significant differences at the (α≤0.05) for teacher's age variable in favor of the younger group. Also, the data showed statistically significant differences at the (α≤0.05) for the variable years of experience in favor of the least experience, less than 5 years.